Detection of some heavy metals and bacterial contamination in canned vegetables - K. Noaman, Hussein; K. Al-Mayaly, Ithar (Iraqi Journal of Science, 2023)
In this paper, thirty six samples of canned vegetables were collected randomly fromdifferent markets in Baghdad city from October 2013 till March 2014. The studyincludes identifying the concentration of some heavy metals (lead, nickel, zinc and iron)by flameless atomic absorption spectrophotometery. It was found that the higherconcentrations of heavy metals in canned vegetables, was lead 1.179 ppm in olive,nickel 0.9078 ppm in olive, while zinc 10.143 ppm green peas and iron 90.601ppm inwhite asparagus; but the lower concentrations represents with lead 0.0021 ppm in greenasparagus, nickel 0.0202 ppm in mushroom, while zinc 0.528 ppm in white asparagusand iron 4.061 ppm in green peas. Canned food has been reported to be contaminatedmainly by spores forming bacteria of the genera Bacillus main sources of a meal. Thebacteria that reported in this study were bacillus spp.